Eyes on me: how social media use is associated with urban Chinese adolescents’ concerns about their physical appearance - Jin, Ruining; Le, Tam-Tri (Frontiers in Public Health, 2024)
Introduction Social media usage carries risks of negative impacts on one’s perception of physical attractiveness, especially among adolescents who are developing their self-image. These findings suggest that targeted interventions focusing on attention-seeking behaviors may be effective in addressing appearance-related anxieties among adolescents. Methods We employed Bayesian analysis with Markov Chain Monte Carlo algorithms on survey data from 11,926 middle school students in China. Findings Our findings indicate that while the amount of daily social media usage does not significantly correlate with appearance concerns, the desire for social media attention through interactions such as liking, commenting, and sharing shows a clear positive association. Female adolescents exhibit a higher degree of concern about their physical appearance compared to males. Additionally, behaviors aimed at improving perceived physical attractiveness, such as exercising and using skin-whitening products, are positively associated with increased appearance concerns. Discussion These findings suggest that targeted interventions focusing on attention-seeking behaviors may be effective in addressing appearance-related anxieties among adolescents.